PENGARUH KUALITAS LAYANAN DAN KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN (Study pada RM. Aldila Semarang) - Ivan Adyatma Putra, 08.05.51.0095; Suko Priyono, Bambang (Students Journal of Economic and Management, 2013)
The study entitled "The Effect of Service and Product Quality to Customer Satisfaction" conducted to analyze customer satisfaction in the Aldila Resto Semarang. The population in this study is customers of Aldila Restowere enjoying the meal and the service provided in restaurants are. Sampling is done by using "accidential sampling", ie the sampling technique based on chance and the number of samples taken as 100.The collected data were analyzed using factor analysis to test the validity of the statement items, Cronbach alpha formula to test the reliability of the instrument, the regression analysis to examine the influence of each partial independent variables were tested with the coefficient of determination and test fit the model to test and prove the influence of the Partial each independent variable. The results of the study are: (1) The results of the statisticallinear regression analysis can be shown by the regression equation Y = 0.130 + 0.850 X1 X2. From the regression equation it is known that the quality of service and product quality has a positive and significant impact on customer satisfaction. (2) The calculation of the coefficient of determination result is 0.717. This shows that the quality of service and product quality variables could explain 71.7% of customer satisfaction, while the remaining 28.3% is explained by other variables not included in this study. (3) The hypothesis that has been done in this study are: a) positive effect on service quality customer satisfaction Aldila Resto Semarang. b) positiveaffect product quality to customer satisfaction Aldila Resto Semarang. In this study the variable quality of the product has a more dominant effect than the variable quality of service.Keyword: Service Quality, Quality Products and Customer Satisfaction.